The Impact of Pre-operative Nutritional Status on Outcomes Following Congenital Heart Surgery - Lim, Carey Yun Shan; Lim, Joel Kian Boon; Moorakonda, Rajesh Babu; Ong, Chengsi; Mok, Yee Hui; Allen, John Carson; Wong, Judith Ju-Ming; Tan, Teng Hong; Lee, Jan Hau (Frontiers in Pediatrics, 2019)
Aims and Objectives: Malnutrition is common in children with congenital heart disease and may contribute to adverse outcomes. This study evaluates the impact of pre-operative nutritional status on outcomes after congenital heart surgery. Methods: We conducted a retrospective cohort study enrolling children under 10 years old who underwent congenital heart surgery at a tertiary children's hospital from 2012 to 2016. Patients who had patent ductus arteriosus ligation only, genetic syndromes, or global developmental delay were excluded. Outcome measures included 30-day mortality, intensive care unit (ICU) length of stay (LOS), hospital LOS, duration of mechanical ventilation, and number of inotropes used post-operatively. We performed univariate/multivariable logistic regression analysis, adjusting for age, cyanotic cardiac lesion, co-morbidity, and Risk Adjustment for Congenital Heart Surgery (RACHS-1) score. Results: Three hundred two children of median age 16.2 [interquartile range (IQR) 3.1, 51.4)] months were included. The most common cardiac lesions were ventricular septal defect (27.8%), atrial septal defect (17.9%), and Tetralogy of Fallot (16.6%). Median weight-for-age z-score (WAZ) was −1.46 (IQR −2.29, −0.61), height-for-age z-score (HAZ) was −0.94 (IQR −2.10, −0.10), and body mass index (BMI)-for-age z-score (BAZ) was −1.11 (IQR −2.19, −0.30). In multivariable analysis, there was an increased risk of 30-day mortality for WAZ ≤−2 vs. WAZ >−2 [adjusted odds ratio (aOR): 4.01, 95% CI: 1.22, 13.13; p = 0.022]. For HAZ ≤-2 vs. HAZ > −2, there was increased risk of hospital LOS ≥ 7 days (aOR: 2.08, 95% CI: 1.12, 3.89; p = 0.021), mechanical ventilation ≥48 h (aOR: 2.63, 95% CI: 1.32, 5.24; p = 0.006) and of requiring ≥3 inotropes post-operatively (aOR: 3.00, 95% CI: 1.37, 6.59; p = 0.006). Conclusion: In children undergoing congenital heart surgery, WAZ ≤ −2 is associated with higher 30-day mortality, while HAZ ≤ −2 is associated with longer durations of hospital LOS and mechanical ventilation, and increased risk of use of 3 or more inotropes post-operatively. Future studies are necessary to develop safe and efficacious peri-operative nutritional interventions, particularly in patients with WAZ and HAZ ≤ −2.